Change it or perish? Drug resistance and the dynamics of livestock farm practices. (October 2018) - Bellet, Camille
Abstract: Farm practices related to drug use in animal agriculture play an important role in the development of drug resistance. In this paper, I use Bourdieu's theory of practice to explore the field of deworming and how the use of deworming medications, also called anthelmintics, by farmers may be a pragmatic choice within the habitus of livestock farming. Drawing on 42 in-depth interviews with livestock farmers across England I show how farmers prioritise farm productivity and animal health and welfare to the detriment of an adequate use of anthelmintics, which may lead to an increase in drug resistance. I also discuss some of the particularities regarding the engagement between farmers, veterinarians and the industry, and how expert advice is commonly limited to one-way flow of information. As a strategy to address drug resistance in livestock, mainstream policy approaches to drug management in the farm have prioritised the development and dissemination of technical guidelines. However, these guidelines are usually disconnected from the farming context, do not take into account the complexity and challenges of farm everyday practices and are eventually rejected by farmers. Although there has been increased interest from the social sciences in studying the intersection between drug resistance and farmers' perceptions and behaviour, there is still a need for unpacking the often hidden dynamics and logics of farm practices, understanding how they shape animal health management and, more specifically, drug use. I argue that farm practices related to drug use are situated within a larger context of intensive animal production systems, which themselves contribute to the emergence of animal diseases, the medicalisation of animal production and drug resistance. Highlights: Farmers' drug practices were analysed using Bourdieu's theory of practice. Anthelmintic use is situated within the 'habitus' of livestock farming. Deworming 'habitus' are shaped by concerns over animal care and productivity loss. Bourdieu's concepts shed light on the pivotal role of drugs in intensive production.